Stagnansi Confidence Building Measures Sebagai Salah Satu Instrumen Penyelesaian Konflik di Asia Tenggara Tahun 1994-2014 - Ni Komang Desy Arya Pinatih (Jurnal Transformasi Global, 2015)
AbstractThis article examines strategy of confidence building measures (CBM) scheme implementation in Southeast Asia region. CBM is one of the main pillars in ASEAN Regional Forum (ARF) other than preventive diplomacy dan conflict resolution that was initiated in 1994. In general, CBM concept refers to the development of mutual trust between both countries in the bilateral, regional or multilateral scheme. There are four (4) aspects for measuring the implementation of a CBM such as: communication measures, constraint measures, transparency measures and verification measures. This paper shows that the implementation of CBM in the Southeast Asian region is not maximized due to the implementation stalled at the level of communication measures, constraint measures and transparency measures, while very minimal verification measures carried out. Another interesting finding is that the level of transparency measures activity of CBM only limited to exchange of intelligence information and the publication of defense white paper, whereas for military exercises and joint military operation ASEAN countries tend to preferring with other countries outside the region such as the United States and China that shows implications for the weak trust building to support the success of CBM. Lack of mutual trust was later implicated in the absence of a common security perspective in the Southeast Asian region and the fact that some ASEAN countries are spoiled by a security umbrella established with countries outside the region (intrusive system).Â Keywords : confidence building mesures, mutual trust, ASEAN, ASEAN Regional Forum